2002
DOI: 10.1111/j.1471-0528.2002.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between amniotic fluid micro‐organism infection and microflora in the mouth

Abstract: Objective To determine whether oral bacteria are found in the amniotic cavity.Design Laboratory based analysis of clinical samples.Setting Royal London Hospital, Whitechapel.Population Forty-eight women attending for elective caesarean section.Methods Dental plaque, a high vaginal swab, amniotic fluid and chorioamnion tissue were taken from women with intact membranes. Main outcome measures Samples were investigated using culture and microscopy for the presence of microorganisms. Amniotic fluid was analysed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
162
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(181 citation statements)
references
References 20 publications
7
162
0
12
Order By: Relevance
“…Moreover, infectious agents are present in the amniotic fluid and membranes of asymptomatic women during amniocentesis (Bashiri et al, 1999). One study (Perni et al, 2004) detected Mycoplasma hominis or Ureaplasma urealyticum in more than 15% of samples of amniotic fluid at the second-trimester, and others have reported the presence of other bacteria (Bearfield et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, infectious agents are present in the amniotic fluid and membranes of asymptomatic women during amniocentesis (Bashiri et al, 1999). One study (Perni et al, 2004) detected Mycoplasma hominis or Ureaplasma urealyticum in more than 15% of samples of amniotic fluid at the second-trimester, and others have reported the presence of other bacteria (Bearfield et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A less appreciated site of F. nucleatum infection is the reproductive tract; the organism can cause both vaginal (Hillier et al 1993;Hitti et al 2001;Holst et al 1994) and intrauterine infections (Altshuler and Hyde 1985;Chaim and Mazor 1992;Digiulio et al 2010). In fact, F. nucleatum is one of the most frequently isolated organisms from amniotic fluid of pregnant women who experience preterm labor (Chaim and Mazor 1992;Hill 1998;Bearfield et al 2002;Hitti et al 2001), and has also been associated with spontaneous miscarriage and stillbirth (Altshuler and Hyde 1985;Chaim and Mazor 1992;Han et al 2010). Periodontal disease, which is thought to affect~40% of reproductive age women (Boggess 2008), has also been linked with increased risks of pregnancy complications such as preterm birth and low birth weight (Offenbacher et al 1996;Dasanayake 1998;Pitiphat et al 2008;Guimaraes et al 2010;Saddki et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium can invade epithelium, endothelium and placental tissues (Han et al, 2000(Han et al, , 2004Saito et al, 2008). It has been detected in relation to high-risk pregnancies, present and past pregnancy complications and, as demonstrated recently, stillbirth (Bearfield et al, 2002;Han et al, 2009Han et al, , 2010Tateishi et al, 2012). Furthermore, studies in animals have confirmed that F. nucleatum is able to translocate via the bloodstream, specifically invade the amniotic tissues and cause fetal death (Han et al, 2004).…”
Section: Introductionmentioning
confidence: 79%